Keberagaman Makanan Terhadap Kejadian Wasting Pada Bayi Usia 0-59 Bulan di Kota Bukittinggi - Triveni (Bunda Edu-Midwifery Journal (BEMJ), 2025)
MDG 1 – Target 1C is to reduce the prevalence of malnutrition in 2015 to ½ of the 1990 situation with a target of 18% malnutrition and only 28.7% was achieved, which can be predicted to increase. By using the FAO1 criteria in measuring minimum consumption needs, only 6% of the Indonesian population has daily consumption below this standard. In the past, the standards used to measure the adequacy of this consumption were slightly too high for Indonesia, so it is indicated that almost 70% of the Indonesian population does not consume enough food. The proportion of the population has also remained relatively unchanged since 1990. Factors that influence the poor nutritional status of toddlers are the adequacy of nutrition and the diversity of food consumed by infants, which ultimately has an impact on death. The purpose of this study was to obtain a description and analysis of the incidence of wasting in toddlers (0-59 months) in Bukittinggi City. This study is an analytical survey study with a case control design. The study was conducted at the Bukittinggi City health center. A quantitative sample of 216 people using the proportionate stratified sampling technique. Chi-square test data analysis. The statistical test results showed that there was a significant relationship between wasting incidence and food diversity (0.028, OR 2.667) in Bukittinggi City. Toddlers who were wasted often occurred in toddlers who consumed food that was not diverse, although there were toddlers who were wasted who had diverse food consumption patterns. This is caused by other factors such as infectious diseases.